Peranan Pengelolaan Arsip Sebagai Pendukung Dalam Kegiatan Akreditasi pada Dunia Pendidikan - S, Sutriani; C, Chalirafi; H, Hamdiah; J, Jumadiah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the role of archive management as a supporter of accreditation activities in the world of education. The problem with archiving that does not comply with procedures is that the documents are irregular and unsafe and difficult to obtain when needed for accreditation purposes by the organization. Apart from that, it is also difficult to be accountable for planning and implementation. Archives have a role as memory centers, sources of information and monitoring tools that are very necessary for every office organization, state institutions, government agencies and state and private universities. The results of the research state that in archiving documents at the educational level studied by the author, some have been carried out well and some have not been carried out well, so it is necessary to manage archives for the purposes of filling out accreditation forms, in order to make it easier, smoother and shorten the time in finding documents again. when needed either by the form assessment team or the assessor team.